Adsorption of phenyl phosphate on Ni-Cr alloy surface: Experimental and theoretical investigations. (4th March 2018) - Naffati, M.; Zanna, S.; Cornette, P.; Costa, D.; Marcus, P.; Abderrabba, M. M.; Somrani, S.
GRAPHICAL ABSTRACT: ABSTRACT: The adsorption behaviour of phenyl phosphate, which is an available biomolecule, on NiCr alloys was investigated. Atomic flame spectroscopy was used to characterize the elemental dissolution during immersion in neutral aqueous solution of 0.09 w% sodium chloride, 37°C. Phenyl phosphate is shown to reduce the release of both Ni 2+ and Cr 3+ ions. XPS analyses evidence the formation of a passive film which is mainly consisted in dichromium trioxide and an ultrafilm layer of phenyl phosphate is adsorbed at the passive film surface. DFT+U calculations show that the phenyl phosphate self-assembling at a Cr2 O3 surface is thermodynamically favoured, with calculated adsorption energy of 2.9 eV. The first half of this value is due to the interaction with the surface, and the second one is due to self-assembling. This study suggests that phenyl phosphate has an important capacity to prevent, in neutral liquid environment, the release of Cr-Ni surface ions thanks to self-assembling in an inner sphere adsorption on the passive film surface. The phosphate group is covalently anchored to the surface. However, the phenyl ring has two roles: (i) it strongly contributes to the self-assembling and (ii) it acts as a hydrophobic function.